The Influence of Safety Culture on Aviation Safety Through the Implementation of Safety Management System in Papua: Case Study of Safety Risk Management and Aircraft Crew Training - Tiara Nugrahayani; Rifqi Raza Bunahri (Dinasti International Journal of Education Management And Social Science, 2024)
This research examines the influence of safety culture on aviation safety through the implementation of the Safety Management System (SMS) in Papua. The focus of this study is on safety risk management and crew training at airports in Papua, which face unique challenges such as extreme weather and difficult terrain. The research method used is quantitative analysis by collecting data through surveys and interviews. The results indicate that the implementation of a strong and effective safety culture can significantly improve aviation safety. Additionally, well-implemented SMS helps in identifying and managing risks and enhancing the quality of training and personnel qualifications. The study also emphasizes the importance of involving all stakeholders, including local communities, to create an environment that supports aviation safety. The implications of this research suggest the need for increased support and investment in infrastructure as well as continuous training to address operational challenges in Papua.